Multi‐model Arlequin method for transient structural dynamics with explicit time integration. (27th April 2017) - Fernier, Alexandre; Faucher, Vincent; Jamond, Olivier
Summary: This paper addresses the explicit time integration for solving multi‐model structural dynamics by the Arlequin method. Our study focuses on the stability of the central difference scheme in the Arlequin framework. Although the Arlequin coupling matrices can introduce a weak instability, the time integrator remains stable as long as the initial kinematic conditions of both models agree on the coupling zone. After showing that the Arlequin weights have an adverse impact on the critical time step, we present two approaches to circumvent this issue. Computational tests confirm that the two approaches effectively preserve a feasible critical time step and show the efficiency of the Arlequin method for structural explicit dynamic simulations. Copyright © 2017 John Wiley & Sons, Ltd.